Integrasi Metode Webqual 4.0 dan Importance Performance Analysis (IPA) untuk Mengukur Kualitas Website Inlis Lite - Putri, Olivia Ananda; Kristiyanto, Daniel Yeri; Safitri, Sisilia Thya (LPPM UNIKA Santo Thomas Medan, 2022)
Integrated Library System (Inlis Lite) is used to facilitate library performance in maximizing service and assist the Library in finding information. The problem on the Inlis Lite website is difficult to access. This study uses the Webqual 4.0 method which focuses on 3 variables namely (usability, information qualit and service interaction) and Importance Performance Analysis (IPA) method. The results of teh Inlis Lite website quality analysis have a conformity rate 88,71% which means that the service is still not satisactory. The average GAP of -0,46 means that the quality of the Inlis Lite website still does not meet user expections. There are 4 indicators that need to be improved quality, namely US5, US7, SIQ5, and SIQ6 which are in the first quadrant